PENGARUH PEMASARAN DIGITAL, MUTU PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ROTI LINA DI TANGERANG SELATAN - Aulya Azmi, Mitha; Tajuddien, Rahadyan (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of digital marketing, product quality and brand image on purchasing decisions for Lina bread. The method used is quantitative. The sampling technique used the ancient rao formula and a sample of 100 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that digital marketing has a significant effect on purchasing decisions with a coefficient of determination value of 44.5% and the hypothesis test obtained t_(count ) > t_(table ) or (8.861 > 1.984). Product quality has a significant effect on purchasing decisions with a coefficient of determination value of 49.6% and the hypothesis test obtained t_(count ) > t_(table ) or (9.819 > 1.984). Brand image has a significant effect on purchasing decisions with a coefficient of determination value of 45.1% and the hypothesis test obtained t_(count ) > t_(table ) or (8.974 > 1.984). Digital marketing, product quality and brand image simultaneously have a significant influence on purchasing decisions with the regression equation Y= 3.624 + 0.302 X₁ + 0.419X₂ + 0.129X. The coefficient of determination value is 55.5% while the remaining 44.5% is influenced by other factors. Hypothesis testing obtained F_(count ) > F_(table ) or (39.943 > 2,700).